Improving Students’ Skill in Writing Recount Text Using Storyboard at The Ninth Grade of Junior High School - Putri Adilah; Amalia Yahya; Rusdiansyah (Institut Agama Islam Negeri Palopo, 2025)
This research attempted to determine the use of Story Board in teaching writing skills in recount text in the ninth grade of SMPN 7 Palopo. This study applied a pre-experimental method. The researcher gets the score on five aspects of writing skills, content, organization, vocabulary, grammar/language use, and mechanics, by using a pre-test and post-test test. The population of this research was the ninth-grade students at SMPN 7 Palopo. There were 19 students as the sample, which is by purposive sampling. This research showed that the mean score of students writing tests in the post-test was 73.21, which is higher than the pre-test score, 60.37. Then the value of tc(tcount)= 7.56 was higher than tt(ttable)= 2.064. It means the alternative hypothesis (H1) is accepted, and (H0) is rejected. It concludes that using a storyboard to improve students' writing skills in recounting text in the ninth grade of SMPN 7 Palopo was effective.